National Survey of US HIV Clinicians: Knowledge and Attitudes About the Affordable Care Act and Opinions of its Impact on Quality of Care and Barriers to Care. (10th June 2020) - McManus, Kathleen A; Ferey, Joshua; Farrell, Elizabeth; Dillingham, Rebecca
Abstract: Background: The Affordable Care Act's (ACA's) major reforms started in 2014. In addition to assessing HIV clinicians' ACA knowledge and attitudes, this study aims to evaluate HIV clinicians' perspectives on whether the ACA has impacted the quality of HIV care and whether it addresses the main barriers to HIV care. Methods: HIV clinicians were emailed a survey weblink in 2018. Descriptive statistics, Mann-Whitney U tests, and binary logistic regression were performed. Results: Of the 211 survey participants, the majority (70%) answered all 4 knowledge questions correctly. About 80% knew correctly whether their state had expanded Medicaid. Participants from Medicaid expansion states were more likely to report an improved ability to provide high-quality care compared with participants from Medicaid nonexpansion states (50% vs 34%; P = .01). The average response to whether the ACA addresses the main barriers to HIV care was neutral and did not differ based on Medicaid status. The top 3 main barriers to HIV care cited were mental health, substance use, and transportation. Conclusions: HIV clinicians in Medicaid expansion states were more likely to report an improved ability to provide high-quality care since ACA implementation compared with those in Medicaid nonexpansion states. However, HIV clinicians across the United States are concerned that the ACA does not address the main barriers to HIV care. To be successful, the "Ending the HIV Epidemic" initiative should address these identified barriers.